Olympic Sports Science—Bibliometric Analysis of All Summer and Winter Olympic Sports Research - Millet, Grégoire P.; Brocherie, Franck; Burtscher, Johannes (Frontiers in Sports and Active Living, 2021)
Introduction: The body of scientific literature on sports and exercise continues to expand. The summer and winter Olympic games will be held over a 7-month period in 2021–2022. Objectives: We took this rare opportunity to quantify and analyze the main bibliometric parameters (i.e., the number of articles and citations) across all Olympic sports to weigh and compare their importance and to assess the structure of the “sport sciences” field. The present review aims to perform a bibliometric analysis of Olympic sports research. We quantified the following topics: (1) the most investigated sports; (2) the main journals in which the studies are published; (3) the main factors explaining sport-specific scientific attractiveness; (4) the influence of being in the Olympic programme, economic weight, and local influences on research output; and (5) which research topic is the most investigated across sports. Methods: We searched 116 sport/exercise journals on PubMed for the 40 summer and 10 winter Olympic sports. A total of 34,038 articles were filtered for a final selection of 25,003 articles (23,334 articles on summer sports and 1,669 on winter sports) and a total of 599,820 citations. Results and Discussion: Nine sports [football (soccer), cycling, athletics, swimming, distance & marathon running, basketball, baseball, tennis, and rowing] were involved in 69% of the articles and 75% of the citations. Football was the most cited sport, with 19.7 and 26.3% of the total number of articles and citations, respectively. All sports yielded some scientific output, but 11 sports (biathlon, mountain biking, archery, diving, trampoline, skateboarding, skeleton, modern pentathlon, luge, bobsleigh, and curling) accumulated a total of fewer than 50 publications. While ice hockey is the most prominently represented winter sport in the scientific literature, winter sports overall have produced minor scientific output. Further analyses show a large scientific literature on team sports, particularly American professional sports (i.e., baseball, basketball, and ice hockey) and the importance of inclusion in the Olympic programme to increasing scientific interest in “recent” sports (i.e., triathlon and rugby sevens). We also found local/cultural influence on the occurrence of a sport in a particular “sport sciences” journal. Finally, the relative distribution of six main research topics (i.e., physiology, performance, training and testing, injuries and medicine, biomechanics, and psychology) was large across sports and reflected the specific performance factors of each sport.